STUDI BIOEKOLOGI PERAIRAN SUNGAI BATU BATU DAN SUNGAI WALANAE UNTUK MENDUKUNG KEGIATAN BUDIDAYA DI DANAU TEMPE KAB.SOPPENG DAN WAJO PROP.SULAWESI SELATAN - Umar, Nur Asia; Mulyani, Sri; Suryani, Ida (Torani Journal of Fisheries and Marine Science, 2017)
Study aim was to determine bioecology aspect of Batu-Batu and Walanae River for supporting aquaculture acitivies at Tempe Lake. Batu-Batu and Walanae Rivers were 2 out of 8 river where affected water quality of Tempe Lake. Research was conducted for 7 months and sampling was conducted for 5 times. Physical water quality parameters were measured in situ while chemical, primary productivity and nutrients parameters were analysed at laboratorium. Results showed that range of temperature and pH were 30.5 – 31.7oC and 7.49 – 7.90, respectively. Range of phytoplankton and zooplankton abundance account for 512 – 2220 cell/L and 40 – 140 ind/L, repectively. Consentration nitrate was range 0.0015 – 0.0452 mg/L, while consentration phosphate was range of 0.015 – 0.1340 mg/L Chlorophyll a concentration was range 0.007 – 2.550 mg/L and primary productivity had range account for 0.10 – 0.89. Based on water quality parameter concluded that Batu-Batu and Walanae River had a significant effect on abundance of phytoplankton and primary productivity. Phosphate and nitrate concentration significantly affected on growth of phytoplankton and zooplankton, so this could be supported for aquaculture activities.